Tuning Wall Thicknesses in Mesoporous Silica Films for Optimization of Optical Anti-Reflective Properties - Abdullah, Nawfel; Hossain, Md Shahriar A; Konstantinov, Konstantin; Tanabe, Hirofumi; Matsuura, Mikiya; Maekawa, Kazuhiko; Fatehmulla, Amanullah; Farooq, Wazirzada Aslam; Islam, Md Tofazzal; Bando, Yoshio; Kaneti, Yusuf Valentino; Yamauchi, Yusuke (Journal of nanoscience and nanotechnology, 2018)
This work reports the fabrication of mesoporous silica films with controllable wall thicknesses by spin coating of precursor solutions consisting of polystyrene-block-polybutadiene-block-polystyrene based triblock copolymers (Hydrogenated methyl Styrene Ethylene Butadiene methyl Styrene, HmSEBmS) and tetraethyl orthosilicate (TEOS) followed by calcination in air at 600 °C, for optical anti-reflection films. By changing the relative weight of the triblock polymer to TEOS, the pore-to-pore distance in the mesoporous silica film can be controlled without significantly affecting the size of the mesopores, thus, enabling effective control of the refractive index and porosity of the films. In terms of optical properties, the transmittance of the fabricated mesoporous silica film is approximately 3.3% higher than that of the uncoated glass substrate in the wavelength range of 400 to 750 nm.